2018
DOI: 10.1590/0047-2085000000187
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety symptoms and body image dissatisfaction in medical students: prevalence and correlates

Abstract: Objective Social anxiety disorder (SAD) and body image dissatisfaction (BID) are common problems among college students, but few studies focused on medical students. We aimed to estimate the prevalence, severity and correlates of SAD symptoms and BID among medical students of a Brazilian public university. Methods A cross-sectional study with 479 students, using structured instruments: Social Phobia Inventory (SPIN), Body Shape Questionnaire (BSQ), and Beck Depression Inventory (BDI). Bivariate analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
3
24
1
7
Order By: Relevance
“…They do not have good friends where they can share all their problems with and prefer not to engage in any social activities [60][61][62]. They tend to doubt their future, and, in some cases, they get into trouble with others [61]. All these findings are consistent with our current results.…”
Section: Psycho-social Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…They do not have good friends where they can share all their problems with and prefer not to engage in any social activities [60][61][62]. They tend to doubt their future, and, in some cases, they get into trouble with others [61]. All these findings are consistent with our current results.…”
Section: Psycho-social Characteristicssupporting
confidence: 91%
“…A previous study showed that students with anxiety disorder tend to avoid all social interaction, isolate themselves, and hardly seek help from others [59]. They do not have good friends where they can share all their problems with and prefer not to engage in any social activities [60][61][62]. They tend to doubt their future, and, in some cases, they get into trouble with others [61].…”
Section: Psycho-social Characteristicsmentioning
confidence: 99%
“…A study with university students from Botucatu, São Paulo State, Southeastern Brazil, observed that one third of students had body image dissatisfaction and they also found a positive association between social anxiety disorder and body image dissatisfaction [29].…”
Section: B O D Y D I S S a T I S F A C T I O N A N D M O O D D I S O mentioning
confidence: 99%
“…In Brazil available studies indicate that this is also a reality 2 . The interest in aspects related to the mental health of this population has been growing, as illustrated in the current issue of the Brazilian Journal of Psychiatry 3,4 .…”
Section: Dear Editormentioning
confidence: 99%